Підсилення gfrp-сітками (тм “mapei”) цегляних конструкцій, що зазнали вогневого впливу - Була, С. С.; Холод, П. Ф.; Богдан, С. М.; Садловська, М. І.; Bula, S.; Kholod, P.; Bogdan, S.; Sadlovska, M. I. (Видавництво Львівської політехніки, 2018)
Впродовж 2017 року в Укрaїнi сталося понад вісімдесят тисяч пожеж. З огляду на це, важливим завданням є підсилення будівельних конструкцій, що зазнали вогневого впливу. Останніми роками у світі поширений новітній метод підсилення конструкцій композитними матеріалами. Зважаючи на швидкість і простоту монтажу та розвиток технологій, що призводять до здешевлення такого способу підсилення, цей напрямок є перспективним та потребує значної кількості досліджень для формування нормативних документів у цій сфері. Досліджено центрально-стиснуті цегляні конструкції, що зазнали вогневого впливу та після цього були підсилені композитними сітками із скловолокна ТМ “MAPEI”. Метою дослідження є верифікація методики розрахунку підсилених конструкцій, що рекомендується виробником, на дослідних зразках після нагрівання. В результаті досліджень отримано інформацію про зміну міцності та деформативності елементів, схеми їх руйнування та ефект підсилення. У майбутньому планується проведення нових експериментів з метою розвитку цього дослідження.

About eighty thousand fires occurred in Ukraine in 2017. Therefore, a strengthening of building structures which were subjected to the fire is an important issue. The modern retrofitting method based on Glass Fiber Reinforced Polymer (GFRP) materials is widely spread over the world. Taking into consideration the speed and simplicity of installing, which lead to price decreasing, this long-term direction needs a significant amount of research for improving standards. This paper is dedicated to research connected to compressed masonry structures strengthened with GFRP mashes (ТМ “MAPEI”) after the fire influence. The aim of the investigation was to verify the common calculation method suggested by guidance on experimental samples after heating. The experimental studies were conducted on clay masonry brick columns that were supposed to 60 min. fire action and strengthened. The special furnace was used for samples heating and heat transfer was analyzed as well. After that axial compressive tests were performed. As the result, new information about deformations diagrams, failure models and strengthening effect was obtained. Presented results are discussed in terms of ultimate strength of masonry samples before and after strengthening. The analysis shows the adequacy of calculation method respectively to fire damaged masonry structures. But some aspects of this design technique are still open. Obviously, additional attention should be paid to deformation of such kind masonry structures as far the modulus of elasticity changes rapidly after the fire. The stress-strain curves and crack patterns were obtained and will be discussed in future articles.
Strengthening of subjected to fire masonry structures with gfrp mashes (tm “mapei”)
Keywords: цегляні конструкції; вогневий вплив; FRP-армування; ефект підсилення; підсилення сітками із скловолокна; masonry structures; fire influence; FRP reinforcing; strengthening effect; strengthening with glass fiber polymer mashes; 624.01/.07